Ragna Crimson. 11 - Kobayashi, Daiki (Manga artist) (Square Enix Manga & Books, 2023)
"On the ground, Chimera undergoes a startling transformation to counteract Borgius's full might. In the sky, Ragna and Kamui exchange deadly blows at speed surpassing light itself. Elsewhere still, Ultimatia's life flashes before her eyes as her fate draws near. The Wingled Bloodline arc reaches its dramatic conclusion!"--back cover.